2015
DOI: 10.1021/acsami.5b00036
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature, Solution-Processed ZrO2:B Thin Film: A Bifunctional Inorganic/Organic Interfacial Glue for Flexible Thin-Film Transistors

Abstract: A solution-processed boron-doped peroxo-zirconium oxide (ZrO2:B) thin film has been found to have multifunctional characteristics, providing both hydrophobic surface modification and a chemical glue layer. Specifically, a ZrO2:B thin film deposited on a hydrophobic layer becomes superhydrophilic following ultraviolet-ozone (UVO) treatment, whereas the same treatment has no effect on the hydrophobicity of the hydrophobic layer alone. Investigation of the ZrO2:B/hydrophobic interface layer using angle-resolved X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…A few examples include c-PVP layers applied to planarize and smoothen the surface of PES or PI, 191,226 as well as PVP films utilized to reduce the surface roughness of PI foils from 3.6 nm down to 0.3 nm (root mean square). 232 145,197 Nevertheless, for solution-deposited metal oxide semiconductors, it is preferable to solution process also the gate dielectric, in order to further benefit from the lowcost large-area approach offered by solution-deposition processes. Within solution-processed gate dielectrics, polymeric materials are especially suitable due to the moderate annealing temperatures needed, as well as the high bendability that can be achieved.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…A few examples include c-PVP layers applied to planarize and smoothen the surface of PES or PI, 191,226 as well as PVP films utilized to reduce the surface roughness of PI foils from 3.6 nm down to 0.3 nm (root mean square). 232 145,197 Nevertheless, for solution-deposited metal oxide semiconductors, it is preferable to solution process also the gate dielectric, in order to further benefit from the lowcost large-area approach offered by solution-deposition processes. Within solution-processed gate dielectrics, polymeric materials are especially suitable due to the moderate annealing temperatures needed, as well as the high bendability that can be achieved.…”
Section: Methodsmentioning
confidence: 99%
“…76,190,191,[194][195][196][197]200,224,228,233 Nevertheless, some groups have presented single bending tests (tensile and compressive) at radii between 25 and 1 mm, as well as cyclic bending up to 10 000 cycles. 83,145,192,193,199,201,[220][221][222]225,226,229,231,232 In the case of flexible TFTs with nano-scale shapes, it has been demonstrated that the application of mechanical bending causes a deformation of the particle network. In particular, tensile strain slightly increases the distance between individual particles, resulting in a lower l FE .…”
Section: Mechanical Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, most of the oxide semiconductors include indium . But the low natural abundance of indium has made it into an increasingly expensive commodity, which has led to a large research driven to replace indium in oxide semiconductors.…”
Section: Introductionmentioning
confidence: 99%